La tula bar - Matus Navarrete, Álvaro Ismael; Gower De Chabert, Nadiya Jihaan (Universidad ESAN, 2016)
This thesis aims to establish an artisanal brewery in Altamira, Managua as business plan to obtain a Master Degree. There has been a noticeable growth concerning the consumption of artisanal beer in Nicaragua. Presently, there are four artisanal beer manufacturers in the country and there appears to be a growing acceptance of this industry by the population. Nevertheless, because the market is still new, there is still room for innovation and diversity concerning the styles of artisanal beer and more so, the product and service offerings that is available to this industry. The objectives of the thesis are to study the domestic market and the feasibility of the business. The brewpub intends to target men and women from the city of Managua between the ages of 24 to 55 and in the low to high class segments.
Keywords: Planificación de la empresa; Estudios de viabilidad; Industria de elaboración de bebidas; Industria cervecera; Bebidas alcohólicas; Bares; Cerveza; https://purl.org/pe-repo/ocde/ford#5.02.04